Human exploitation of adult horseshoe crab and public awareness campaign in Hong Kong SAR, China - Pui Yi Tang; Hei Wut Fong; Shan Yee Lee; Wing Tung Chang; Lee Yan Pang; Tin Yan Hui; Kelvin Jun Yin So (Global Ecology and Conservation)
In Hong Kong, studies on trading and human exploitation of adult Asian horseshoe crabs (Carcinoscorpius rotundicauda and Tachypleus tridentatus) are limited, with the last study dating back to 2005–2006. To identify how trading activities (e.g., for consumption as food, bycatch, and mercy release activities) may threaten horseshoe crab populations in recent times, market surveys were conducted at five potential horseshoe crab trade outlets in Hong Kong in 2020 – 2021 in tandem with phone interviews with Hong Kong citizens to measure their knowledge/awareness on horseshoe crabs and relevant conservation measures. We also conducted in-depth interviews with 15 representatives from fishers’ associations and 20 from religious organisations on their views on horseshoe crab status in fisheries and mercy release. The market survey recorded a total of 80 adult horseshoe crabs for sale in seafood restaurants or fish stalls out of the 98 shops surveyed. In addition, phone interviews revealed a low level of awareness among Hong Kong citizens (N = 1005 respondents), with 53 % having no prior knowledge and never heard of “horseshoe crab”. However, such knowledge improved with an increased education level, particularly among those in the 50–59 age group and those who visited horseshoe crab habitats. Nearly all respondents (975) pledged not to consume horseshoe crabs upon being informed of their conservation status. Representatives from the fishers’ association reported that while there were no targeted fisheries for horseshoe crabs in Hong Kong, a small quantity of horseshoe crabs were captured as bycatch. Among the 12 religious organisations surveyed, 30 % of the respondents still conducted mercy release activities in Hong Kong. Some strongly disagreed with the need for government interventions on mercy release and were not willing to accept alternative official approaches. The above results revealed a considerable knowledge and awareness gap among the public and identified anthropogenic threats to Asian horseshoe crabs. To alleviate the situation, a pilot public awareness campaign was launched to increase public awareness and promote the conservation of horseshoe crabs in Hong Kong. We recommend strengthening the protection of local Asian horseshoe crabs through a combination of conservation management and public education.